2008
DOI: 10.1590/s0104-42302008000600020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de dermatoses em idosos residentes em instituição de longa permanência

Abstract: *Correspondência:Rua Professor João Arruda, 45 -Bairro Perdizes São Paulo -SP CEP 05012-000 RESUMO OBJETIVOS. Determinar a prevalência das afecções dermatológicas em 75 idosos residentes em instituição de longa permanência na cidade de Santos-SP, e confrontar os achados com revisão da literatura. MÉTODOS. Setenta e cinco idosos foram submetidos a exame dermatológico. Com os dados obtidos calculou-se a prevalência, o número médio por paciente e a freqüência de dermatoses. Foi ainda analisado a distribuição nos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…16 In this study less than 50% of caregivers at the post-test identified the cause and treatment of scabies, which may be associated with a lack of prior knowledge and for being community-dwelling elderly.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…16 In this study less than 50% of caregivers at the post-test identified the cause and treatment of scabies, which may be associated with a lack of prior knowledge and for being community-dwelling elderly.…”
mentioning
confidence: 75%
“…Scabies, another common disorder, is a contagious disease caused by mite Sarcoptesscabiei, exclusive of human skin. [1][2][3] Venous ulcers are lesions on the lower limbs and may have different etiologies, common in patients with diabetes, venous insufficiency or arterial insufficiency. 4 Diabetic foot is a complication resulting from metabolic disorder and long duration of diabetes mellitus which contribute to the development of peripheral neuropathy, leading to decreased sensitivity of the feet, callus formation and, consequently, ulcers.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…A melanose solar caracteriza-se por manchas hipercrômicas pequenas, de limites bem nítidos e número variado, que surgem no adulto geralmente após a quarta década, em áreas fotoexpostas, o que corrobora com este estudo, uma vez que a maior parte dos participantes encontrava-se com mais de 30 anos. A melanose solar também foi indicada como a dermatose mais frequente segundo a queixa secundária em uma casuística com pacientes da quarta idade (acima de 80 anos) [20]; foi a dermatose significativamente mais prevalente em indivíduos com mais de 60 anos de idade residentes em uma instituição filantrópica de longa permanência no município de Santos, seguida da ceratose seborreica [21]; e uma das três alterações mais frequentes na pele de pescadores profissionais de Recife, submetidos a radiação solar crônica prolongada [22].…”
Section: Artigo Originalunclassified
“…Photoaging is correlated with chronic exposure to the sun's rays, leading to several types of senile alterations, as well as the susceptibility of the individual to benign or malignant neoplasia. 3 Most studies of the skin of elderly individuals deal with adherence to the use of sunscreen, 4 the development of ulcers in intensive care units (ICU), 5 nursing diagnoses of the skin, 6 ultraviolet and carcinogenic radiation, 7 skin modifications in the elderly, versus photoaging, 8 sunscreens, 9 the aging process and assistance for the elderly, 10 and the study of age-related modifications to human skin using histomorphometry and autofluorescence. 11 Considering the abovementioned phenomena, as well as the potential neglect of the skin by elderly individuals during their lives, this section of the population is more at risk of developing lesions and soft tissue diseases.…”
Section: Introductionmentioning
confidence: 99%